The Influence of Health Promotion Strategies on Community Participation in The Prevention of Non-Communicable Diseases at Ujong Fatihah Health Center, Nagan Raya District - Kurniawan, Muhammad Fadlin; Nababan, Donal; Anita, Surya; Santoso, Heru; Sitorus, Priska (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
Efforts to prevent non-communicable diseases can be carried out through health promotion activities. Through health promotion strategies carried out, it is expected to be able to increase community participation in the prevention of non-communicable diseases. Community participation is widely believed to be beneficial for the development, implementation, and evaluation of health services. However, there are still many challenges to successful and sustainable community involvement. The purpose of this study was to see the effect of health promotion strategies on community participation in preventing non-communicable diseases. The research method used was analytic with a cross-sectional approach. The number of samples in this study was 218 people. The data analysis used is Chi-Square Test. Based on the results of multivariate analysis, it show that the correlation value of community empowerment (0.354), the correlation value of atmosphere building (0.179), the correlation value of advocacy (0.643), and the correlation value of partnership (0.150). The conclusion is that the variable that has a high correlation with community participation is advocacy, the variable that has a moderate correlation with community participation is community empowerment and the variable that has a very low correlation with community participation is the atmosphere building and partnership variables. Suggestions are expected for health workers, especially at the Ujong Fatihah Health Center, to be able to increase community empowerment through regular meetings held in the context of preventing infectious diseases, building a good atmosphere with the community, including the community in every advocacy process and building good partnerships with the community by involving the community in every advocacy activity carried out